Out–of–plane capillary pressure of technical textiles. (September 2019) - Willenbacher, Björn; May, David; Mitschang, Peter
Abstract: Textile permeability characterization often follows an unsaturated approach, i.e. a dry textile is impregnated by a fluid and flow front movement is monitored. For permeability calculation based on Darcy's law, a pressure-driven injection is commonly applied. Depending on flow velocity, capillary pressure can also contribute to flow movement, which would lead to a calculation error if not considered. This again requires capillary pressure determination. In the present work, a novel measurement system for out-of-plane capillary pressure based on weight increase was developed and applied to characterize the out–of–plane capillary pressure of a random mat, a twill 2/2 woven fabric, and a biaxial non-crimp fabric (all glass fiber) at three different fiber volume contents. Silicone oil was used as measurement fluid. Capillary pressures ranged between 150 and 225 Pa.